2022
DOI: 10.21203/rs.3.rs-1992367/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single Cell Analysis Identifies Distinct Profiles in Pediatric Acute Respiratory Distress Syndrome

Abstract: Acute respiratory distress syndrome (ARDS), termed pediatric ARDS (pARDS) in children, is a severe form of acute respiratory failure (ARF) that is associated with significant morbidity and mortality. Pathologic immune responses have been implicated in the development of pARDS. Here, we present a unique description of microbial sequencing and single cell gene expression in tracheal aspirates (TAs) obtained longitudinally from infants admitted to the pediatric intensive care unit (PICU) with ARF. Important alter… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 60 publications
(93 reference statements)
0
4
0
Order By: Relevance
“…Moreover, these earlier data showed that this hybridisation panel of approximately two million capture probes designed in 2015 was suited for the detection of novel coronaviruses by reactivity with other vertebrate betacoronavirus probes 10 . During the past years, this specific hybridisation panel distributed by Roche has been adopted in a broad range of different clinical 15,[22][23][24][25][26][27][28][29] and zoonotic settings 22,29,30 is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review)…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, these earlier data showed that this hybridisation panel of approximately two million capture probes designed in 2015 was suited for the detection of novel coronaviruses by reactivity with other vertebrate betacoronavirus probes 10 . During the past years, this specific hybridisation panel distributed by Roche has been adopted in a broad range of different clinical 15,[22][23][24][25][26][27][28][29] and zoonotic settings 22,29,30 is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review)…”
Section: Introductionmentioning
confidence: 99%
“…One recent study using bulk mRNAseq to evaluate the nasal epithelial transcriptome of PARDS patients found that one subgroup of patients had loss of epithelial stem cells genes and those patients had a longer course of PARDS 9 . Another analysed tracheal aspirates of intubated PARDS patients using single‐cell RNAseq and found a subset of monocytes that expressed repair related transcripts 10 . These monocytes were more common in patients with a lower level of illness severity and were hypothesised to be critical for the clearance of pro‐inflammatory cells thus paving the way for repair and regeneration 10 .…”
mentioning
confidence: 99%
“…9 Another analysed tracheal aspirates of intubated PARDS patients using single-cell RNAseq and found a subset of monocytes that expressed repair related transcripts. 10 These monocytes were more common in patients with a lower level of illness severity and were hypothesised to be critical for the clearance of pro-inflammatory cells thus paving the way for repair and regeneration. 10 Additionally, there is evidence that cross talk between multiple different reparative macrophage phenotypes may help promote repair and regeneration in pediatric patients with severe lung injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation